Bone marrow-derived cells do not contribute significantly to collagen I synthesis in a murine model of renal fibrosis. - Roufosse, C; Bou-Gharios, G; Prodromidi, E; Alexakis, C; Jeffery, R; Khan, S; Otto, W; Alter, J; Poulsom, R; Cook, H (2006)
Interstitial fibroblasts play a central role in kidney fibrosis. Their origin is debated, with recent data indicating a contribution of bone marrow (BM)-derived cells to the expanded population of interstitial cells after kidney damage in animals and humans. This study investigated whether these BM-derived cells would respond appropriately to a fibrotic drive by producing collagen. A transgenic mouse that expresses both luciferase and beta-galactosidase reporter molecules under the control of a 17-kb promoter and enhancer element of the gene encoding the alpha2 chain of the collagen I was used. Male transgenic BM was transplanted into female wild-type C57BL/6 mice (n=14), and unilateral ureteric obstruction was performed later to induce renal fibrosis. In the obstructed kidney of the BM-chimeric female mice, a mean of 8.6% of smooth muscle actin-positive interstitial cells were Y chromosome positive. Increased collagen I mRNA in the obstructed kidney was detected by in situ hybridization. No luciferase activity was detected by enzyme assays in tissue homogenates of BM recipients, and very few luciferase mRNA transcripts were seen, mainly in tubular cells. beta-Galactosidase activity was not a useful reporter molecule because it could not be distinguished from enhanced endogenous beta-galactosidase activity in the obstructed kidney. These results indicate that BM-derived interstitial cells do not make a significant contribution to collagen I synthesis in the context of renal injury.